Prevalence, spectrum, and the relations between short-term and long-term post-acute sequelae of COVID-19 in children - Elena R. Meskina; Marima K. Khadisova; Anna Y. Ushakova; Elena E. Tselipanova; Lidiya A. Galkina (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Background. Data on the prevalence of post-COVID-19 condition (PCC) in children differ due to the lack of specific diagnostic criteria, reliable biomarkers, and limitations of many studies. It is important to study the association between PCC, previous functional disorders, and any events in the post-acute period of COVID-19 to estimate the true burden of PCC in children.